The Impact of SFIC Spritual Accompaniment to Work Motivation and Nurses’ Caring Behavior at ST. Vincentius Hospital Singkawang - Mestoly, Ester; Leo Bunga, Asnet; Priyo Hastono, Sutanto (International Journal Labs, 2024)
This research is motivated by the complex role of nurses in nursing services that require periodic refreshments to maintain motivation in providing attentive services. In this context, SFIC (Sisters of the Franciscan of the Immaculate Conception) spiritual accompaniment is relevant because it can uplift, motivate, and remind nurses of the vocation and meaning of their profession. This study aims to determine the effect of SFIC spiritual assistance on nurses' work motivation and caring behavior in the inpatient unit. The research method used is Quasi-Experimental Control Group Pretest Posttest Design. Control and intervention groups were determined using total sampling. Data analysis was conducted using the Paired T-test and Independent T-test, with results showing significant differences between the intervention and control groups in nurses' work motivation and caring behavior after receiving SFIC spiritual assistance. The results showed significant differences between the intervention and control groups in work motivation (p = 0.001) and caring behavior of nurses (p = 0.0001) after receiving SFIC spiritual assistance. This is also supported by the ANCOVA test results, which show a significant effect of intervention methods on increasing nurses' work motivation and caring behavior after controlling for confounding variables. This study implies that spirituality can motivate and improve nurses' caring behavior when providing nursing services. As a suggestion, spiritual assistance can be used as one of the activities in the hospital training program to strengthen motivation and the quality of nurse services.